The Impact of Age and Social Class on the Strength of Derbyshire Accent - Rathauská, Karolína (Univerzita Pardubice, 2019)
The aim of this work is to describe the differences between Derbyshire accent and Received Pronunciation. In the theoretical part, the most significant contrasts between Derbyshire accent and General British are scrutinized and the current sociophonetic research is summarised. The practical part aims to either confirm or disprove the following assumption: the older the person is and the lower their social class, the more prominent their accent is going to be. The research is based on phonetic analysis of recordings that were taken from participants who are originally from, or from nearby, the county of Derbyshire. Acoustic and auditory analysis is done by using specialised software Praat. The data has then been interpreted in relation to two sociophonetic variables: age and social class of the speaker.
Analýza akcentu Derbyshire s ohledem na věk a sociální status uživatelů
Keywords: accent; Derbyshire; RP English; sociophonetics; social class; age group; accent variations; přízvuk; hrabství Derbyshire; britský standard (RP); sociofonetika; společenský status; věk; variance přízvuků